2023
DOI: 10.1162/jocn_a_02025
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Size Encodes Uncertainty during Exploration

Abstract: Exploration is an important part of decision making and is crucial to maximizing long-term rewards. Past work has shown that people use different forms of uncertainty to guide exploration. In this study, we investigate the role of the pupil-linked arousal system in uncertainty-guided exploration. We measured participants' pupil dilation (n = 48) while they performed a two-armed bandit task. Consistent with previous work, we found that people adopted a hybrid of directed, random, and undirected exploration, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In recent years, there has been converging evidence showing dissociable neural implementation underlying these two explorative strategies in the human brain. The first line of research comes from studies supporting the differential role of dopamine and noradrenaline in mediating exploration [Chakroun et al, 2020, Cremer et al, 2023, Dubois et al, 2021, Fan et al, 2023. Pharmacological intervention (manipulation) in human participants supports the hypothesis that dopamine mediates direct exploration [Chakroun et al, 2020, Cremer et al, 2023, while norepinephrine controls random exploration [Dubois et al, 2021, Fan et al, 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been converging evidence showing dissociable neural implementation underlying these two explorative strategies in the human brain. The first line of research comes from studies supporting the differential role of dopamine and noradrenaline in mediating exploration [Chakroun et al, 2020, Cremer et al, 2023, Dubois et al, 2021, Fan et al, 2023. Pharmacological intervention (manipulation) in human participants supports the hypothesis that dopamine mediates direct exploration [Chakroun et al, 2020, Cremer et al, 2023, while norepinephrine controls random exploration [Dubois et al, 2021, Fan et al, 2023.…”
Section: Introductionmentioning
confidence: 99%
“…The first line of research comes from studies supporting the differential role of dopamine and noradrenaline in mediating exploration [Chakroun et al, 2020, Cremer et al, 2023, Dubois et al, 2021, Fan et al, 2023. Pharmacological intervention (manipulation) in human participants supports the hypothesis that dopamine mediates direct exploration [Chakroun et al, 2020, Cremer et al, 2023, while norepinephrine controls random exploration [Dubois et al, 2021, Fan et al, 2023. The second line of research comes from studies that showed the dissociable role of the right frontopolar cortex (rFPC) and dorsolateral prefrontal cortex (rDLPFC) in controlling direct and random exploration, respectively.…”
Section: Introductionmentioning
confidence: 99%